Studi Kadar Cholinesterase dalam darah Petugas Fogging di Kabupaten Bantul Tahun 2016 - Hendrika Puspita Sari; Sarjito Eko Windarso; Achmad Husein (Poltekkes Kemenkes Yogyakarta, 2016)
DHF is one of public health problems in Yogyakarta Province and is endemic in three out of the five regencies/city. One of control efforts undertake by health agencies is pesticide fogging, that employ several active ingredients, one of which is organophosphate, that can cause poisoning if mis-appropriately used. The study wanted to know the level of cholinesterase in blood as a sign of poisoning, by conducting an analytical cohort survey, towards 20 fogging personnels of Bantul Regency. Cholinesterase levels were measured by using tintometer kit and cholinesterase kit. Meanwhile, data which were related to study subjects were obtained primarily by direct observation and through secondary sources. Study results show that in recess, all personnels indicate normal cholinesterase level, but after do the fogging 20 % of them exhibit mild poisoning. It is also revealed that 50 % o the personnels are aged 41-50 years, 45 % had educationlevel of senior high school or bachelor degree, 75 % had long service period, 70 % rarely do the fogging, 85 % had good practice when do the fogging, and 55 % did not wear complete protecting devices. The data analysis using Spearman correlation test at 95 % level of significance concludes that factor which is significantly correlated with cholinesterase level is the frequency of fogging (p value = 0,027 and correlation coefficient = 0,494 or fair association). The other variables under study show no significant correlation, i.e. age (p value = 0,715), education level (p value = 0,462), service period (p value = 1,000), fogging practice (p value = 0,374), and completeness of protecting device (p value = 0,447).